Solute effects on edge dislocation pinning in complex alpha-Fe alloys - Pascuet, Maria Ines Magdalena (2017)
Reactor pressure vessel steels are well-known to harden and embrittle under neutron irradiation, mainly because of the formation of obstacles to the motion of dislocations, in particular, precipitates and clusters composed of Cu, Ni, Mn, Si and P. In this paper, we employ two complementary atomistic modelling techniques to study the heterogeneous precipitation and segregation of these elements and their effects on the edge dislocations in BCC iron. We use a special and highly computationally efficient Monte Carlo algorithm in a constrained semi-grand canonical ensemble to compute the equilibrium configurations for solute clusters around the dislocation core. Next, we use standard molecular dynamics to predict and analyze the effect of this segregation on the dislocation mobility. Consistently with expectations our results confirm that the required stress for dislocation unpinning from the precipitates formed on top of it is quite large. The identification of the precipitate resistance allows a quantitative treatment of atomistic results, enabling scale transition towards larger scale simulations, such as dislocation dynamics or phase field.